On the effect of manual rework in AFP quality control for a doubly-curved part. (15th December 2021) - Sacco, Christopher; Brasington, Alex; Saidy, Clint; Kirkpatrick, Max; Halbritter, Joshua; Wehbe, Roudy; Harik, Ramy
Abstract: It is widely thought that considerable manual rework is a necessity in the production of aerospace composite structures manufactured through automated fiber placement (AFP). However, there is limited availability of information regarding the precise quality control outcomes obtained through manual rework and defect removal. Given the large amounts of cycle time dedicated to the rework process, it may be fruitful to investigate in what ways rework may improve part quality, shift defect distributions, or in some cases, fail at improvement and make the resulting structure worse. To provide insights into these questions, a ply of a doubly-curved part was produced by AFP, inspected using an automated inspection system, manually repaired, and then inspected again. Through a multi-faceted analysis of the inspection data, trends including changes in defect number and significance, repair suggestions, and a previously unreported new defect type associated with manual rework can be observed.